Development of polysulfone /silver oxide membranes for separation of natural organic matters - Yunos, Muhamad Zaini (2014)
In this present work, the development of polysulfone (PSf)/silver oxide membrane was conducted with the used of silver oxide as hydrophilic additives, polyethylene glycol (PEG) as pore forming agent and 2,4,6-triaminopyrimidine (TAP) as a compatibilizer for separation natural organic matters (NOM). The PSfIsilver oxide membranes were characterized based on their contact angle, thermal behaviour, tensile strength and morphology. The results were correlated with membrane performance for NOM separation. The NOM samples used in this study were collected from Sembrong river water in Parit Raja, Johor, Malaysia. The addition of silver oxide was found to increase membrane hydrophilicity and improved water permeability up to 323 liter per meter hour (LMH) for 1.5 wt. % silver oxide content. Silver oxide also has improved membrane antifouling properties. The effect of PEG as a pore forming agent in PSflsilver oxide membrane was investigated by manipulating PEG content fiom 8 wt. % to 16 wt. % at fixed concentration of PSf, silver oxide and TAP. It was observed that high PEG concentration improved the water permeation properties of the membrane. Tensile strength increment, silver oxide aggregation reduction, low silver loss during immersion and permeation confirmed that TAP had successfully enhanced compatibility between PSf and silver oxide. TAP has also improved rejection and antifouling of the membrane against NOM. The entrapment of silver oxide in PSf membrane was proved using Fourier transform infrared (FTIR) and X-ray diffraction (XRD). However, TAP was found to decrease membrane permeability. Therefore, the optimization of membrane formulation was carried out using response surface methodology (RSM), wherein the main responses were pure water flux and NOM rejection. The optimum amount of each component for membrane fabrication was found to be 10.58 wt. % PEG, 2.0 wt. % silver oxide and 0.3 wt. % TAP. The average confirmation run of experimental results for this optimum formulation was 356 LMH permeation and 94.38 % rejection, which was only 5.90 % and 1.48 % off respectively from predicted results.